Religious Support of European Archeological Projects in the Nineteenth Century - Jasim, Haidar (Opción, 2019)
The archeology of the Near East was one of the important areas that attracted the interest of Europeans in modern history, since archeology was founded since the beginning of its emergence in the first decade of the nineteenth cen- tury on the basis of political predominantly, it was the arena of this science is the region of the Near East, the East is clearly linked In areas controlled by the Ottoman Empire, whether under its direct or moral control - for example, Egypt - or neighboring regions such as Persia, it is difficult to separate the ar- chaeological activities sponsored by France, as a forerunner in this area, from the opposing political projects developed by the great powers at the time, in order to achieve benefit. Archeology and its development clearly overlapped with the foreign policies of European countries in general, and the internal po- litical situation and its impact on the establishment and guidance - later - the activities of individuals and scientific and academic institutions in the form of Special.